Analysis of Customer Experience and Customer Satisfaction on Repurchase Intention with Customer Loyalty as a Mediation Variable at Cafe Dokobox Mamuju - Wardani, Rezki; Wiyadi , Wiyadi; Soepatini, Soepatini; Nasir, M. (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This article discusses customer experience and customer satisfaction regarding repurchase interest at Cafe Dokobox Mamuju, with customer loyalty as a mediating variable. This research used a questionnaire to collect data from 200 customers and analyzed using SmartPLS 3. The results show that customer experience and customer satisfaction have a significant influence on loyalty, customer experience also influences repurchase intention. However, customer loyalty does not mediate the influence of customer experience and satisfaction on repurchase intention.